2016
DOI: 10.1155/2016/4170923
|View full text |Cite
|
Sign up to set email alerts
|

Synovial Lipomatosis of the Glenohumeral Joint

Abstract: Synovial lipomatosis (also known as lipoma arborescens) is a rare and benign lesion affecting synovium-lined cavities. It is characterized by hyperplasia of mature fat tissue in the subsynovial layer. Although the most commonly affected site is the knee joint, rarely additional locations such as tendon sheath and other joints are involved. We present a case of synovial lipomatosis of the glenohumeral joint in a 44-year-old man. The clinical data radiological studies and histopathologic results are described, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(23 citation statements)
references
References 19 publications
1
21
0
1
Order By: Relevance
“…A systematic review on the arthroscopic treatment of LA of the knee revealed a satisfactory short-term outcome [ 15 ]. The present study supports similar findings: patients may benefit from less invasive arthroscopic procedures when feasible, as arthroscopic treatment of shoulder [ 2 , 3 , 28 , 35 , 36 ] and elbow lesions [ 13 ] led to promising short-term outcomes. Although LA was recognized as a clinical entity decades ago, the evidence is scarce and long term outcome data are unavailable.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…A systematic review on the arthroscopic treatment of LA of the knee revealed a satisfactory short-term outcome [ 15 ]. The present study supports similar findings: patients may benefit from less invasive arthroscopic procedures when feasible, as arthroscopic treatment of shoulder [ 2 , 3 , 28 , 35 , 36 ] and elbow lesions [ 13 ] led to promising short-term outcomes. Although LA was recognized as a clinical entity decades ago, the evidence is scarce and long term outcome data are unavailable.…”
Section: Discussionsupporting
confidence: 90%
“…Soft tissue mass in the subacromial space measuring 2.5 × 1.0 × 0.5 cm Kawashima et al [ 3 ] 1 Shoulder (subdeltoid) Xray: normal Arthroscopic synovectomy and RC repair 9 No Occasional aching, good function MRI: subdeltoid fluid villous projections, full-thickness supraspinatus tear Paccaud and Cunningham [ 13 ] 1 Elbow (intraarticular) Xray: no Arthroscopic synovectomy and posterior humeroulnar decompression 14 No Full ROM. Asymptomatic MRI: large intra-articular multilobulated pseudo-tumoral mass causing posterior humeroulnar impingement with mixed components including lipomatous and synovial fringes Lim et al [ 35 ] 1 Shoulder (subacromial, subdeltoid) Xray: bony spurs in the acromion and greater tuberosity Arthroscopic bursectomy, lipoma excision, acromioplasty, and RC repair 5 No Asymptomatic MRI: Partial-thickness bursal tear of the supraspinatus tendon, subacromial-subdeltoid bursa fluid-distended-fat like nodular projections, greater tuberosity, and lateral acromion osteophytes Beyth and Safran [ 2 ] 1 Shoulder (intraarticular) Xray: Hill Sachs Arthroscopic synovectomy and lipoma e...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Si bien la presentación más usual es una condición monoarticular que afecta a la rodilla, con predilección por la bolsa suprapatelar, en la literatura también encontramos casos clínicos que hacen referencia a otras localizaciones, ya sea con presentación mono o biarticular: cadera, tobillo, codo, muñeca, pie y hombro [4][5][6][7][8] . La bolsa subdeltoidea es una localización poco frecuente del lipoma arborescente y solo se han descrito unos pocos casos en la literatura 8 .…”
Section: Discussionunclassified
“…4 Treatment options include open and arthroscopic synovectomy. [5][6][7][8][9] As it is a rare entity with less than 100 cases reported so far, the clinical, radiological and pathological data available is very limited and varied. 3 The purpose of our study is to contribute to the literature the clinical details (age, gender, clinical presentation), radiological and ORIGINAL ARTICLE histological features of the cases reported at our centre in the last decade and provide a better understanding of this condition to physicians, radiologists and pathologists.…”
Section: Introductionmentioning
confidence: 99%